Post-Translational Modifications of p53 in Ferroptosis: Novel Pharmacological Targets for Cancer Therapy - Zhang, Le; Hou, Ningning; Chen, Bing; Kan, Chengxia; Han, Fang; Zhang, Jingwen; Sun, Xiaodong (Frontiers in Pharmacology, 2022)
The tumor suppressor p53 is a well-known cellular guardian of genomic integrity that blocks cell cycle progression or induces apoptosis upon exposure to cellular stresses. However, it is unclear how the remaining activities of p53 are regulated after the abrogation of these routine activities. Ferroptosis is a form of iron- and lipid-peroxide-mediated cell death; it is particularly important in p53-mediated carcinogenesis and corresponding cancer prevention. Post-translational modifications have clear impacts on the tumor suppressor function of p53. Here, we review the roles of post-translational modifications in p53-mediated ferroptosis, which promotes the elimination of tumor cells. A thorough understanding of the p53 functional network will be extremely useful in future strategies to identify pharmacological targets for cancer therapy.